2019
DOI: 10.1175/jhm-d-17-0234.1
|View full text |Cite
|
Sign up to set email alerts
|

NCA-LDAS: Overview and Analysis of Hydrologic Trends for the National Climate Assessment

Abstract: Terrestrial hydrologic trends over the conterminous United States are estimated for 1980–2015 using the National Climate Assessment Land Data Assimilation System (NCA-LDAS) reanalysis. NCA-LDAS employs the uncoupled Noah version 3.3 land surface model at 0.125° × 0.125° forced with NLDAS-2 meteorology, rescaled Climate Prediction Center precipitation, and assimilated satellite-based soil moisture, snow depth, and irrigation products. Mean annual trends are reported using the nonparametric Mann–Kendall test at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 85 publications
0
18
0
5
Order By: Relevance
“…For example, the observed increases in the eastern US are consistent with land-atmosphere feedbacks and the complementary relationship of evaporation (Bouchet 1963;Brutsaert 1982), whereby under non-water limited conditions, ETo and actual evapotranspiration (ETa) are expected to converge as atmospheric demand for water is met by additional water provided by increased ETa, thereby lowering ETo. Observed increases in ETa in this region (Jasinski et al 2019) may be further enhanced by agricultural intensification in places like the Central US (Brown and Degaetano 2013). At the same time, Accepted for publication in Journal of Hydrometeorology.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, the observed increases in the eastern US are consistent with land-atmosphere feedbacks and the complementary relationship of evaporation (Bouchet 1963;Brutsaert 1982), whereby under non-water limited conditions, ETo and actual evapotranspiration (ETa) are expected to converge as atmospheric demand for water is met by additional water provided by increased ETa, thereby lowering ETo. Observed increases in ETa in this region (Jasinski et al 2019) may be further enhanced by agricultural intensification in places like the Central US (Brown and Degaetano 2013). At the same time, Accepted for publication in Journal of Hydrometeorology.…”
Section: Discussionmentioning
confidence: 89%
“…Although studies have found general agreement of trends in evaporative demand across the CONUS, most studies have typically been based on one set of forcing conditions (Ficklin et al 2016(Ficklin et al , 2015McCabe and Wolock 2015;Vicente-Serrano et al 2020), or a limited number of ground observations (Groisman et al 2004;Lawrimore and Peterson 2000;Hobbins et al 2004;Szilagyi et al 2001). Likewise, other studies have focused on trends in actual evapotranspiration (ETa; Walter et al 2004;Jasinski et al 2019)the flux of water transferred from the land surface to the atmosphere, rather than evaporative demand. And while several studies have been conducted to assess trends in individual variables that contribute to evaporative demand including temperature (Vose et al 2012), wind (Vautard et al 2010;Pryor et al 2009;Zhang et al 2019;Fan et al 2020), solar radiation (Augustine et al 2019), and humidity (Ficklin and Novick 2017;Brown and Degaetano 2013;Alter et al 2018;Seager et al 2015), differences in analytical approaches, datasets, and time periods analyzed make it difficult to ascertain how these may collectively influence changes in evaporative demand.…”
mentioning
confidence: 99%
“…2017), the U.S. Air Force 557th Weather Wing LDAS, and the National Climate Assessment Land Data Assimilation System (Jasinski et al. 2019; Kumar, Jasinski, et al. 2019).…”
Section: Methods: Overview Of Wldasmentioning
confidence: 99%
“…In this paper, daily soil moisture (0-100 cm depth) and surface water with a 0.125°resolution from the National Climate Assessment -Land Data Assimilation System Noah 3.3 Version 2 (NCA-LDAS) ( Jasinski et al, 2018 were used to isolate the groundwater signal and elucidate from which TWS any significant changing signal originates (Equation ( 1)).…”
Section: Methodsmentioning
confidence: 99%